2014
DOI: 10.2147/ahmt.s57950
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of utilization of a no-cost HIV transition clinic: a cross-sectional study of young adults living with HIV/AIDS

Abstract: There is minimal research that has been conducted among young adults to understand the determinants of the utilization of human immunodeficiency virus (HIV) health services in this population. The purpose of this study was to explore the levels and determinants of HIV transition clinic (HTC) services utilization by young adults living with HIV/acquired immunodeficiency syndrome (YALHA). The study used a cross-sectional design and quantitative methods to collect data from a sample of 379 YALHA between the ages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Initial transition preparation ranged from time of diagnosis to late teen years. The age for transition (25 years) proposed by participants in this study is older than the late teen or early twenties reported in most studies . Other studies proposed initiation of transition according to the youth’s level of maturity and self‐management capability .…”
Section: Discussionmentioning
confidence: 57%
“…Initial transition preparation ranged from time of diagnosis to late teen years. The age for transition (25 years) proposed by participants in this study is older than the late teen or early twenties reported in most studies . Other studies proposed initiation of transition according to the youth’s level of maturity and self‐management capability .…”
Section: Discussionmentioning
confidence: 57%
“…Médecins sans Frontières has also piloted a Youth Clubs program in Cape Town, including a structured interactive activity‐based session rooted in peer support that has been endorsed in the South African national adherence policy. Few interventions, however, have been described in the peer‐reviewed literature and evaluations have not looked at retention in care as an outcome . This is one of the first studies to date to look at the impact of an adolescent focused differentiated model of care on ART retention.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find any national guidelines specifying an age for transition; however, in practice, we observed from available data that transition tends to occur across a wide age range (e.g. 13–22 years), with most occurring after 18 years [29], 20 years [35,39], or 22 years [40]. While chronological age is a standard criterion, it is also important to consider the age of maturity of the patient; in other disciplines, providers suggest that age of maturity may vary depending on social support, education, and learning capabilities [38].…”
Section: Implementation Of Youth-friendly Models Of Care For Transitimentioning
confidence: 99%
“…June 2011 POC CD4 cell-count testing was introduced in youth clinic. Both had 3 ART preparation counselling session– Group B more receive CD4 cell count test result and their eligibility assessed (90% vs. 67%; relative risk [RR] = 2.4, 95%CI:1.8–3.4, p  < 0.0001)– No significant difference in the proportion starting and completing ART preparation counselling sessions 56% vs. 58% ( p  = 0.9).– 8 days reduction in the time from HIV testing to ART initiation in Group B, ( p  = 0.6).– The proportion of eligible patient who initiated ART was 44% and 50% ( p  = 0.6) in group A and group B, respectively, and a similar proportion were retained on therapy at three months after initiation (RR = 1.0, 95% CI:0.5–1.2, p  = 0.9)– No difference in the proportion of patients lost to follow-upNyabigambo,Adolescent health, Medicine and Therapeutics2014, AIDS care 2014 [40,46]Kampala,UgandaCross-sectional design and quantitative methods to collect data to study the levels (regular/irregular) and determinants (personal, health service delivery and community) of HIV transition clinic (HTC) services utilization by adolescents and young adults living with HIV379 adolescents and young adults 15–24 years, registered clients at an HTC between March and June 2012Infectious disease institute, with Wednesday monthly visits,and providing clinical examination, laboratory services, prevention mother-to-child transmission services, family planning services, treatment of sexually transmitted infections, ART psychosocial support, counselling, home visiting, peer support services, skills building programmes– 32% were regular utilizers of the HTC, mean age 22 years, 61% currently on ART.– 82% of regular utilizers were femalesNo relationship between reported wellbeing (measured with General Well-Being Schedule, 18-point scale) and attending all clinical visits (compared to missing at least one visit)– The most utilized services were: clinical examination (96%), laboratory (87%) and counselling (70%),– The less utilized: home visiting (6%,) peer support (20%).Individual correlates of HTC utilization– urban location: regular 56% vs. irregular 69%, p  = 0.016– age 15–19: regular 15% vs. irregular 9%, p  = 0.044– currently on ART: regular 82% vs. irregular 51%, p  = 0.000– last CD4 < 250: regular 37% vs. irregular 18%, p  = 0.000Community correlates:– not having a caregiver at home: regular 11% vs. irregular 22%, p  = 0.014Health services delivery correlates– no receiving counselling: regular 20% vs. irregular 36%, p  = 0.001Multivariable analysis: CD4 > 251 (adjusted Odds Ratio [AOR] = 0.58 95% CI = 0.36–0.95), not being on ART (AOR = 0.47, 95% CI = 0.15–0.47), not receiving counselling (AOR = 0.47, 95% CI = 0.27–0.83)McKenney, 2016 unpublished [39]Lilongwe, MalawiAssessment of a Transition Training programme, in Baylor College teen Clubs800 adolescents, 18–24 years, 106 graduate participants, from 2013 to 20156-week Transition Training programme to transfer to adolescents economic, psychosocial, and self-care skills needs to make a successful transition into adulthoodMean age: 20 years23% have disclosed their HIV status to friends/partners; 25% were enrolled in secondary school, and 3% in university; 10% found employment, 8% were involved as ambassadors for...…”
Section: Implementation Of Youth-friendly Models Of Care For Transitimentioning
confidence: 99%
See 1 more Smart Citation